Le labyrinthe dans les arts du XXe siècle. Les arts du XXe siècle dans le labyrinthe - Escorne, Marie (Amaltea. Revista de Mitocrítica, 2009)
The mythical figure of the labyrinth is often echoed in twentieth century artistic practices. First, it is called upon by artits who wish to introduce a participative dimension in the way the work of art will be apprehended. The creators of Dylaby – a group creation subtitled « A Dynamic Labyrinth » - turn a full museum into a maze, whereby they upset the visitors’ habits of perception and cognition. After they, too, had created labyrinthic routes (Labyrinth, 1963 ; Labyrinth II, 1964), the members of the Groupe de Recherche d’Art Visuel (Research Group on Visual Art) carry on with the questioning of the traditional viewer-work-of-art relationship by going outside museums, inviting citizens to envision Paris as a beyond scale labyrinth (One Day in the Street, 1966). The myth of the labyrinth is thus reconsidered through works – whether playful or disturbing – of visual artists whose material is the very city. Posing as a Theseus groping for the way out (Stanley Brouwn) or a Minotaur on the alert (Vito Acconci) or again as an Ariadne weaving a thread destined to benumbed, sleep-walking and habit-ridden passers-by (Francis Alÿs), these artists show that fiction and fables can always be reachable behind the tame appearance of reality.